2016
DOI: 10.1007/s00421-016-3359-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exercise under different levels of blood-flow restriction on muscle activation and fatigue

Abstract: Muscular activation, as well as neuromuscular fatigue, varies as a function of relative BFR intensity. Therefore, the individual determination of vascular restriction levels is crucial before engaging in BFR exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 36 publications
13
89
0
3
Order By: Relevance
“…This implies on the preserved ability to increase volitional activation of larger number of motor units to compensate for the decrease in force capacity, which in turn resulted in significantly longer times of sustained contraction compared to SHAM-BFR group. The results are in line with consensus in the literature that BFR exercise implicates greater muscular activation to maintain the same work output (Moritani et al, 1992; Takarada et al, 2000; Wernbom et al, 2009; Yasuda et al, 2009; Cook et al, 2013; Fahs et al, 2015; Loenneke et al, 2015; Fatela et al, 2016). Hypothetically, these increments in EMG amplitude may reflect an enhanced recruitment of type II motor units (Moritani et al, 1992; Takarada et al, 2000; Moore et al, 2004) due to the local accumulation of metabolites (Loenneke et al, 2015) or increase in eccentric muscle activity (Wernbom et al, 2009) during exercise with BFR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies on the preserved ability to increase volitional activation of larger number of motor units to compensate for the decrease in force capacity, which in turn resulted in significantly longer times of sustained contraction compared to SHAM-BFR group. The results are in line with consensus in the literature that BFR exercise implicates greater muscular activation to maintain the same work output (Moritani et al, 1992; Takarada et al, 2000; Wernbom et al, 2009; Yasuda et al, 2009; Cook et al, 2013; Fahs et al, 2015; Loenneke et al, 2015; Fatela et al, 2016). Hypothetically, these increments in EMG amplitude may reflect an enhanced recruitment of type II motor units (Moritani et al, 1992; Takarada et al, 2000; Moore et al, 2004) due to the local accumulation of metabolites (Loenneke et al, 2015) or increase in eccentric muscle activity (Wernbom et al, 2009) during exercise with BFR.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies, investigating the interaction between BFR exercise and patterns of neuromuscular activation, have shown that acute BFR exercise augments neural activation and recruitment of type II motor units (Moritani et al, 1992; Takarada et al, 2000; Moore et al, 2004). Pierce et al (2006), and more recently also Fatela et al (2016), demonstrated that higher levels of BFR elicited greater decrements in median frequency of rectus femoris, vastus lateralis, and vastus medialis muscle in a short period after exercise, which implies that the magnitude of neuromuscular fatigue is substantially larger following this form of exercise. A progressive increase in type II motor unit recruitment and reduction in fatigue would therefore be expected to be the primary long-term adaptation of BFR training.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the current study found similar exercise-induced fatigue and EMG amplitude, regardless of the BFR condition. In contrast, a previous study found that the change in EMG amplitude and fatigue following BFR exercise was dependent upon the level of the cuff inflation pressure (Fatela et al, 2016). The discrepancy in findings between studies may be attributed to several methodological differences.…”
Section: Emg Amplitudementioning
confidence: 65%
“…Our results showed that EMGFmed reduced significantly, remaining lower than PRE exercise values within 3 minutes after the task failure only in PO condition. This finding indicates a slower recovery of neuromuscular fatigue [39] when the used exercise is carried out with PO. Moreover, this finding is in line with previous International Journal of Applied Exercise Physiology www.ijaep.com studies where the EMGFmed was shifted toward low frequencies immediately after exercise with vascular occlusion, remaining with this characteristic up to 2 minutes after the exercise conclusion [39][40][41].…”
Section: Median Frequency Of the Emg Signalmentioning
confidence: 85%